\(2004A=\frac{2004^{2004}+2004}{2004^{2004}+1}=1+\frac{2003}{2004^{2004}+1}\)
\(2004B=\frac{2004^{2005}+2004}{2004^{2005}+1}=1+\frac{2003}{2004^{2005}+1}\)
\(\frac{2003}{2004^{2004}+1}>\frac{2003}{2004^{2005}+1}\)
\(\Rightarrow2004A>2004B\)
\(\Rightarrow A>B\)
2004A=\(\frac{2004^{2004}+2004}{2004^{2004}+1}\)
\(\frac{2004^{2004}+2004}{2004^{2004}+1}-1=\frac{2003}{2004^{2004}+1}\)
2004B=\(\frac{2004^{2005}+2004}{2004^{2005}+1}\)
\(\frac{2004^{2005}+2004}{2004^{2005}+1}-1=\frac{2003}{2004^{2005}+1}\)
Ta thấy :\(\frac{2003}{2004^{2004}+1}>\frac{2003}{2004^{2005}+1}\)
=> \(2004A>2004B\)
Vậy \(A>B\)